2013
DOI: 10.1155/2013/792840
|View full text |Cite
|
Sign up to set email alerts
|

1,4-dihydroxy-2-naphthoic Acid Induces Apoptosis in Human Keratinocyte: Potential Application for Psoriasis Treatment

Abstract: Psoriasis, which affects approximately 1–3% of the population worldwide, is a chronic inflammatory skin disorder characterized by epidermal keratinocytes hyperproliferation, abnormal differentiation, and inflammatory infiltration. Decrease in keratinocyte apoptosis is a specific pathogenic phenomenon in psoriasis. Chinese herbs have been used for the treatment of psoriasis in China showing promising effect in clinical trials. A traditional Chinese medicine has relatively fewer side effects with longer remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
(101 reference statements)
1
15
0
1
Order By: Relevance
“…The subgroup for this disease mainly includes psoriasis vulgaris (also called plaque psoriasis), pustular psoriasis, psoriatic arthritis and erythrodermic psoriasis clinically [3,4], characterized by excessive growth of the epidermal layer of the skin, chronic inflammation in the dermis and parakeratosis [5]. Currently, the aetiology of psoriasis is not fully understood, but genetics, cell apoptosis and proliferation, immunity, inflammation and neurotransmitters are reported to be involved [6][7][8]. Although typical medications of psoriasis involve retinoid acids [9], methotrexate [10], cyclosporine [11], compound glycyrrhizin [12], few of them have targeting effects because of the complexity of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The subgroup for this disease mainly includes psoriasis vulgaris (also called plaque psoriasis), pustular psoriasis, psoriatic arthritis and erythrodermic psoriasis clinically [3,4], characterized by excessive growth of the epidermal layer of the skin, chronic inflammation in the dermis and parakeratosis [5]. Currently, the aetiology of psoriasis is not fully understood, but genetics, cell apoptosis and proliferation, immunity, inflammation and neurotransmitters are reported to be involved [6][7][8]. Although typical medications of psoriasis involve retinoid acids [9], methotrexate [10], cyclosporine [11], compound glycyrrhizin [12], few of them have targeting effects because of the complexity of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriatic keratinocytes are prone to resist against apoptosis, and it may be one of principal pathogenic mechanisms of psoriasis (Kaštelan et al, ). It was reported that the alleviation of psoriasis can be predicted from the apoptotic effects in HaCaT cells (Mok, Xie, Sham, Lin, & Cheng, ; Sun, Han, Zhao, Zhu, & Hu, ). The apoptotic effect of ACE was identified by the externalization of phosphatidylserine in HaCaT cells as shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…Cell cycle arrest assay was performed in HaCaT cells after incubating with ACE (Figure f). The antipsoriatic properties of natural products have been assessed by the cell cycle arrest assay in HaCaT cells (Mok et al, ; Tse, Cheng, Che, Zhao, & Lin, ). The apoptotic potential of ACE in HaCaT cells was evaluated by the alteration of subG0/G1 population percentage in cell cycle arrest assay (Mok et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is the selective process of physiological cell deletion that regulates the balance between cell proliferation and cell death. The failure of apoptosis is considered to contribute to the development of certain human diseases, such as psoriasis, non-alcoholic fatty liver disease and acute myelogenous leukemia (22,23).…”
Section: Introductionmentioning
confidence: 99%